Quality of Personnel Administration Services at the Personnel and Human Resource Development Agency: JEL Classification: H83, J45, I18, D73, M12 - Nia Agus Setiawati; M. Nasir Hamzah; Mujahid Yunus (Newinera Publisher, 2026)
This study aims to describe the quality of civil servant administration services based on the perception of Civil Servants (ASN) and to identify internal and external factors influencing these services. The research adopted a descriptive qualitative approach, supported by quantitative data obtained through Likert scale questionnaires targeting ASNs who visit BKPSDM for civil servant administration services. Data collection also involved in-depth interviews with BKPSDM officials, as well as field observations and documentation studies. Qualitative data were analyzed thematically, while quantitative data were analyzed descriptively. The research findings indicate that the overall quality of civil servant administration services at BKPSDM Nunukan Regency is in the good to very good category, with the majority of ASNs expressing satisfaction to high satisfaction. The main strengths of the service were identified in the aspects of staff friendliness and courtesy, and the availability and comfort of service facilities. Nevertheless, there are still areas requiring improvement, namely in the clarity and accessibility of information regarding procedures and requirements, as well as the transparency of information concerning estimated service completion times. Significant internal factors influencing service quality include human resources (staff competence and motivation), service systems and procedures, and the utilization of information technology and infrastructure. Meanwhile, external factors that also contribute are changes in laws and regulations, ASN expectations and demands for digital services, and advancements in information technology. Recommendations proposed to enhance service quality include improving the clarity and accessibility of information through digital platforms, optimizing service completion efficiency and transparency, developing civil servant administration service applications, and improving service facility spaces.